A rapid method for selection and cloning of stably transformed insect cell lines - Khanefard, Najmeh; Mekvichitsaeng, Phenjun; Akeprathumchai, Saengchai; Roshorm, Yaowaluck M.; Poompusta, Kanokwan (Asia-Pacific Journal of Science and Technology, 2021)
Insect cell lines have been widely used for recombinant protein production due to their abilities in eukaryotic-type post-translationally modifications of proteins and simple culture process. Stably transformed insect cells can be engineered by delivery of the target gene to integrate randomly into the insect cell chromosome, they are then able to stably express this gene and continuously produce recombinant protein. To ensure maximum recombinant protein production, selection of the highest recombinant protein producing cells by cell cloning technique is recommended. A limiting dilution method is generally used for cell cloning, however it is inefficient and time consuming. A rapid cell cloning method for transformed cells selection was therefore developed. A bi-cistronic transfer vector was constructed for gene delivery and co-expression of fusion gene between the target gene, T2A peptides and red fluorescent protein (RFP) encoded genes in insect cells. T2A peptides induce ribosomal skipping during translation thus allowing separation of the target recombinant protein and RFP. Thus, the red florescent cell should be the recombinant protein producing cells and could be easily separated and selected. To validate this vector, an influenza virus neuraminidase gene (NA) was used as a target gene. After 24 hours post transfection, red fluorescent cells were readily observed and selected. Single target cell selection could be achieved within 7-10 days which was 2-3 times more rapid than the original cell cloning process. All cloned cells could stably express the NA gene for at least 22 passages.